2016
DOI: 10.1097/ta.0000000000001115
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional study of hemostatic gauze and tourniquets in rural civilian trauma

Abstract: Therapeutic study, level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 10 publications
2
54
0
14
Order By: Relevance
“…On the basis of recent studies by te Grotenhuis et al and Leonard et al, hemostatic agents seem to be efficacious in adjunctive control of bleeding in the prehospital civilian setting. The total number of applications of hemostatic gauze in both studies was small, however 18,19…”
Section: Discussionmentioning
confidence: 92%
“…On the basis of recent studies by te Grotenhuis et al and Leonard et al, hemostatic agents seem to be efficacious in adjunctive control of bleeding in the prehospital civilian setting. The total number of applications of hemostatic gauze in both studies was small, however 18,19…”
Section: Discussionmentioning
confidence: 92%
“…Of the studies reporting demographics, there were 366/446 (82%) male patients, and the average age ranged from 22 to 59 years. One study presented an injury severity score 31. Three studies presented physiological parameters,13 28 34 with two studies comparing these between the haemostatic group and the comparator 13 28.…”
Section: Resultsmentioning
confidence: 99%
“…However, the evidence was based on lower-level human (case series and reports) and animal (swine models with various vascular injuries) studies. A multi-institutional retrospective analysis of clinical outcomes following prehospital use of Combat Gauze found that it was 89% effective for hemorrhage control and associated with minimal morbidity in rural civilian trauma across a wide range of wounds on the head or face, upper and lower extremities, and junctional regions [141]. A prospective report of 30 prehospital uses of Combat Gauze in a civilian setting showed 73% cessation of bleeding and 20% reduced bleeding [142].…”
Section: Combat Gauzementioning
confidence: 99%